The Library association year book for 1891-. - MacAlister, John Young Walker, Sir, 1856-1925; Pacy, Frank; Inkster, Lawrence; Jast, L. Stanley (Louis Stanley), 1868-1944 (The Association, 1891)
The year book for 1914 includes "List of public (rate supported) libraries of the United Kingdom. (Revised to December, 1913)" and "Principal libraries of the British dominions and colonies, India, and Egypt" (p. 115-130)